Capital Markets Study III : Functions of capital markets - Organisation for Economic Coopertaion and Development (Paris : O.E.C.D., 1969)
The main objective of this report is to consider the main causes of differences in interest rate levels and interest rate structures. Another is to discover what important defects might be remedied in order to improve the organization of national markets and to enable them operate more efficiently in matching the supply and demand for funds.
osc 10/05/17
Loans
Keywords: Capital Markets